Continuous drive friction welding of 5A33 Al alloy to AZ31B Mg alloy. (January 2017) - Liang, Zhida; Qin, Guoliang; Geng, Peihao; Yang, Fan; Meng, Xiangmeng
Graphical abstract: Highlights: The continuous drive friction welding of Al alloy to Mg alloy was realized. A continuous intermetallics layer formed along the friction interface. The IMCs formation resulted from diffusion transformation. The highest strength of Al/Mg joint can reach up to 101 MPa. Abstract: 5A33 aluminum alloy bar was joined with AZ31B magnesium alloy bar by continuous drive friction welding. The friction weldability of Al alloy to Mg alloy was investigated. The microstructure of the friction interface in joints was analyzed by optical microscopy, scanning electron microscopy, and X-ray diffraction analysis. The chemical compositions of newly formed phase on the interface were tested by energy dispersive spectroscopy. The results show that the sound joints of Al alloy to Mg alloy can be obtained by continuous drive friction welding process. The tensile strength of the joints increased with increasing friction time, and on average the highest strength could reach up to 101 MPa when friction time was 5 s. All the friction welded samples failed at the friction interface during tensile test. The fracture appearances showed almost flat surface, so the fracture of the as-welded Al/Mg joints in this experiment was brittle mode. A new reaction layer formed on the friction interface consisted of intermetallic compounds (IMCs) layer and Mg solid solution layer, and the IMCs were mainly Mg17 Al12 and Al3 Mg2 . The type of IMCs was variable with increasing friction time. Due to high microhardness of reaction layer, the microhardness value on the interface was dramatically larger than that of the Mg base material. The thickness of hardened layer in the Mg side and softened layer in the Al side increased with increasing friction time.